Descriptions of the immature stages of four species of Phyllophaga, Paranomala and Macrodactylus (Coleoptera: Melolonthidae) from Los Altos de Chiapas, Mexico - Ramírez-Salinas, Concepción; Morón, Miguel Ángel; Castro-Ramírez, Adriana E. (Instituto de Ecología, A.C., 2011)
Third instar larvae of Phyllophaga pilosula (Moser), Paranomala denticollis (Bates), Paranomala trapezifera (Bates) and Macrodactylus fulvescens Bates and the pupa of the latter species, are described with specimens from San Cristobal de Las Casas, Amatenango del Valle and Yalumá-Villahermosa in Comitan, Chiapas, Mexico. Adults of Phyllophaga and Paranomala species were captured and reared in captivity to obtain third-stage larvae. Through the development of third stage larvae of M. fulvescens collected from soil with corn crops, were obtained exuvia of third instar larva, pupae and adults. Drawings of the diagnostic structures and brief comments on the differences with local related species are included.